Women's education, contraception use, and high-risk fertility behavior: A cross-sectional analysis of the demographic and health survey in Ethiopia - Woldeamanuel, Berhanu Teshome; Gessese, Getachew Tilahun; Demie, Takele Gezahegn; Handebo, Simegnew; Biratu, Tolesa Diriba (Frontiers in Global Women's Health, 2023)
Background: Women who begin childbearing at an early age often have a greater number of children, and this, in turn, is linked to adverse maternal, infant, and child health outcomes. Short birth intervals and higher birth order are also associated with infant and child mortality. Thus this study attempt to look into the link between women's education, contraception use, and high-risk fertility behavior in Ethiopia. Methods: Data was extracted from the 2019 Ethiopian interim Demographic and Health Survey. A total of 5,846 women were included in the analysis. Multivariable logistic regression analysis was used to quantify the effect of predictor variables with having HRFB. A 95% Confidence Interval of Odds ratio excluding one was reported as a significant association with HRFB and predictor variables. Results: About 72.8% (95% CI 71.6–73.9%) of women have high-risk fertility behavior. Of those thirty-two percent have single high-risk fertility behavior and 40.8% have multiple high-risk fertility behavior. Of that high-risk fertility behavior, 58.7% birth orders more than three, 22.4% short birth interval (less than 24 months), 35.1% older age (higher than 34 years) and 1.6% were early age (less than 18 years). No education 4.3 (AOR=4.31; 95% CI 2.09, 8.89), and primary education 2.71(AOR=2.71; 95% CI 1.63, 4.50) more likely to experience high-risk fertility behavior, compared with women who had higher education. Every year increase of years of schooling reduced the odds of high-risk fertility behavior by 6% (AOR=0.94; 95% CI 0.89, 0.98). Use of modern contraception (AOR=0.74; 95% CI 0.622, 0.879) and knowledge of modern contraception methods (AOR=0.80; 95% CI 0.66, 0.96) associated with reduction of risk of HRFB. Conclusions: Educating women and encouraging women to use modern contraceptives are vital ingredients that should be included in all policies aiming to reduce maternal and neonatal deaths by averting the risk of HRFB.